Dementia as a manifestation of degenerative diseases of nervous system: controversial questions of pathogenesis, prospects of treatment and prevention - N. S. Makarov; T. O. Kolokolova; O. V. Kolokolov; V. V. Yudina; E. V. Lukina (Лечащий Врач, 2021)
The article covers dementia in elderly patients and Alzheimer’s disease as the most frequent reason of dementia. Clinical manifestations and diagnostic criteria for Alzheimer’s disease were considered, as well as approaches to its treatment.